Kolumbovo jajce antropologije - Volarič, Tina (Etnolog. Nova vrsta (Ljubljana), 2009)
In recent decades, anthropology has revised itself several times, evaluated the access codes to its knowledge, and detected new options for the use of ethnographic experiences. Rather than addressing past re-examinations of the ethnographic research method, the article tackles the issue of the method of anthropological research. It addresses interpretive methods, the issue of empathy, the shifts between the concepts of field and home, the dilemmas of recording ethnographic experiences, and, finally, ethical reservations; regarding the latter, I have come to the conclusion that they are not necessarily impediments, but can act as a stimulus to the question how to understand the world and how to put our understanding in words.
Keywords: Volarič, Tina, 1980-; etnografija; ethnography; anthropology; antropologija; terensko delo; zapisovanje; interpretacija; ethics; etika